(untitled) (Bangladesh Critical Care Journal, 2019)
Background: High prevalence of Chronic heart failure due to Idiopathic Dilated Cardiomyopathy (DCM) is animportant cause of heart failure in Bangladesh. This study was carried out to find the clinical characteristics of thepatients with Idiopathic DCM, so that the data can be used to treat symptoms and improve survival and treatment. Methodology: This prospective observational study was carried out in the Department of Cardiology, BIRDEMGeneral Hospital, Dhaka, Bangladesh from January 2012 to December 2018. Total 50 consecutive admittedpatients fulfilling the criteria of Idiopathic DCM were studied. Clinical information, findings fromEchocardiography and other relevant investigations were collected for analysis. Results: Among total 50 patients, 30(60.0%) were male and 20(40.0%) were female. Majority 20(40.0%) patientsbelonged to age 51-60 years and their mean age was found 55.34±13.24 years. Using NYHA (New York HeartAssociation) functional status classification of the patients, 18(36.0%) patients were found in NYHA class I,15(30.0%) in class II, 12(24.0%) in class III and 5(10.0%)in class IV. Almost all patients presented with three basicsymptoms i.e. exertional dyspnea, easy fatigability and pedal edema. Orthopnea, Paroxosmal Nocturnal Dyspnoea(PND), palpitation & chest pain wewe also reported in almost half of the patients. Mean pulse was found88.78±15.75 beat/min, respiratory rate 20.79±6.48 breath/min, BMI 23.12±3.29 kg/m2, systolic BP 119.03±22.22mmHg and diastolic BP 75.00±12.54 mmHg. Bilateral basal crepitation 45(90.0%), Pedal edema 43(86.0%),Raised JVP 39(78.0%), Hepatomegaly 35(70.0%) were also found. Third heart sound in 34(68.0%), Pan systolicmurmur of Mitral regurgitation 40(80.0%), Pansystolic murmur of Tricuspid regurgitation was present in42(84.0%) among study patients. Mean left ventricular ejection fraction was found 30.44 ±4.91%, LVIDs 5.24±0.51cm and LVIDd 6.18 ±0.52 cm. Conclusion: Majority of the Idiopathic DCM patients belonged to age 51-60 year age group with malepredominance and clinical presentation was variable. Bangladesh Crit Care J September 2019; 7(2): 86-89